Differences in self-perception of adolescents in relation to the affiliation of the individual or collective sports - Korovljev, Darinka; MadiÄ‡, Dejan; PopoviÄ‡, Boris; ObradoviÄ‡, Borislav; PopoviÄ‡ StijaÄiÄ‡, Milica; Å obot, Ivona (Arena-Journal of Physical Activities, 2017)
This survey was conducted in the total sample of 128 adolescent of both sex and average age of 18.75 years by using adapted questionnaireProfile of self- perception for adolescents (Harter, 1988). The main objective of this study was to investigate the psychological characteristics of adolescents, candidates for admission to the Faculty of Sport and Physical Education, and to deter- mine the differences in these characteristics of candidates according to the type of sport – individual or collective. The results of ttest for Independent Samples showed that there are statistically significant differences between participants in scores on the self-concept dimensions depending on the sport they practice. Candidates who are engaged in team sports had significantly higher score on the dimension of Social Acceptance than the participants who are engaged in individual sports.